PENGGUNAAN PELURU KLASTER (CLUSTER MUNITION) YANG DILAKUKAN ARAB SAUDI DI YAMAN DITINJAU DARI HUKUM INTERNASIONAL - Muhammad Faris; Suhaidi Suhaidi; Sutiarnoto Sutiarnoto (Journal of USU International Law, 2020)
ABSTRACT CLUSTER MUNITION CLUSTER USED BY SAUDI ARABIA IN YAMAN VIEWED FROM INTERNATIONAL LAW Muhammad Faris Prof.Dr.Suhaidi, SH., MH** Sutiarnoto, SH.,M.Hum*** War is inevitable. Therefore, a legal arrangement was made regulating war, which is now known as International Humanitarian Law (International Humanitarian Law or IHL). The legal arrangements governing war are aimed at ensuring that a war is not carried out indefinitely. One of the restrictions placed on international humanitarian law is the use of permitted weapons. International humanitarian law prohibits the use of weapons of mass destruction in armed conflict. Issues that will be discussed in this study are first, How is the regulation of International Law and the role of the United Nations in solving the problem of war crimes; second, how to regulate the use of Cluster Munition according to International Law; third, how is the regulation of International Law on the issue of using the Cluster Munition used by Saudi Arabia in the conflict in Yemen. The writing method used in this study is a normative juridical method which is carried out by examining library materials and secondary data, which in this case is the applicable international legal norms governing the prohibition of using Cluster Bullets as contained in various International Law instruments. The results of this study indicate that the Saudi Arabian Coalition has been proven to use various cluster bullets as weapons in excessive armed conflict in Yemen according to International Humanitarian Law. The use of cluster bullets in military attacks carried out by the Saudi Arabian Coalition against the Houthis also had a negative impact on society in Yemen. Cluster Bombs are very threatening to civilians, for two reasons; the area effect is very broad, and will leave many unexploded bomblets so dangerous for human lives. According to International Humanitarian Law, Cluster Bullets are also prohibited because they violate military requirements and humanitarian principles. Because international law has the characteristic of not being able to be imposed on countries, it is therefore recommended that Saudi Arabia be given a sanction in the form of revocation of certain rights, for example closing the opportunity to become a UN security council for several years. Keywords: War Crimes, Saudi Arabia, Cluster Munition, Cluster Bullets